2019
DOI: 10.3390/cells8050507
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Immunity between Adenoviruses and Hepatitis C Virus (HCV): Recombinant Adenovirus Vaccine Vectors Containing Antigens from Unrelated Pathogens Induce Cross-Reactive Immunity Against HCV Antigens

Abstract: Host immune responses play an important role in the outcome of infection with hepatitis C virus (HCV). They can lead to viral clearance and a positive outcome, or progression and severity of chronic disease. Extensive research in the past >25 years into understanding the immune responses against HCV have still resulted in many unanswered questions implicating a role for unknown factors and events. In our earlier studies, we made a surprising discovery that peptides derived from structural and non-structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
0
9
0
2
Order By: Relevance
“…Adenovirus vectors based on human serotype 5 of species C are widely used as gene delivery vehicles that enabled high-titer production and highly efficient gene transfer into targeted cells. 27 The oncolytic adenovirus carrying therapeutic genes has shown to exert promising antitumor effects on different types of cancers. [28][29][30] In our study, we used the AdEasy system 31 to construct new recombinant adenovirus Ad-RGD-Survivin-ZD55-miR-143: replacing the original E1A promoter with tumor-specific Survivin promoter could transcriptionally control viral replication; deleting the E1B-55kDa region could lose the ability to replicate in normal cells; and inserting an RGD motif into the HI loop of the adenovirus knob could elevate the infection efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirus vectors based on human serotype 5 of species C are widely used as gene delivery vehicles that enabled high-titer production and highly efficient gene transfer into targeted cells. 27 The oncolytic adenovirus carrying therapeutic genes has shown to exert promising antitumor effects on different types of cancers. [28][29][30] In our study, we used the AdEasy system 31 to construct new recombinant adenovirus Ad-RGD-Survivin-ZD55-miR-143: replacing the original E1A promoter with tumor-specific Survivin promoter could transcriptionally control viral replication; deleting the E1B-55kDa region could lose the ability to replicate in normal cells; and inserting an RGD motif into the HI loop of the adenovirus knob could elevate the infection efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that there may be heterologous immunity due to a protein in SARS CoV-2 that is homologous to a protein in Mycobacterium bovis . Such heterologous immunity has been documented between other pathogens, such as adenovirus and hepatitis C virus [ 10 ]. The presence of such immunity between a SARS-CoV-2 capsid protein and a protein of Mycobacterium bovis would allow for a much stronger and specific immunity against the virus subsequent to BCG vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be investigated whether Ad-specific effector-memory T cells provide the immediate defense when exposed to infecting HCV, and whether they form at least a partial basis for the 15–30% spontaneous clearance of HCV observed in humans. In a follow up report, we demonstrated that cross-reactive cellular and humoral immune responses against HCV antigens core, NS3, and NS5 are also induced upon immunization with various recombinant Ads containing antigens from HCV, Mycobacterium tuberculosis , HIV, and EBOV (94). Intriguingly, the nature of the transgene antigen had a significant impact on the levels of cross-reactive immunity induced against HCV antigens (94).…”
Section: Vaccine Vectors In the Context Of Heterologous Immunitymentioning
confidence: 95%
“…In a follow up report, we demonstrated that cross-reactive cellular and humoral immune responses against HCV antigens core, NS3, and NS5 are also induced upon immunization with various recombinant Ads containing antigens from HCV, Mycobacterium tuberculosis , HIV, and EBOV (94). Intriguingly, the nature of the transgene antigen had a significant impact on the levels of cross-reactive immunity induced against HCV antigens (94). It is possible that Ad also has cross-reactivity with other pathogens, but this has not been explored yet.…”
Section: Vaccine Vectors In the Context Of Heterologous Immunitymentioning
confidence: 95%